ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENERIMA BEASISWA BIDIKMISI DI IAIN SULTAN THAHA SAIFUDDIN JAMBI - Guswarni, Nelwi; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2017)
Bidikmisi educational assistance is given to students who Excel and has limited the ability of the economy. Organizers of the program bidikmisi is the universities and private colleges who have selected Kopertis under the Ministry of research, technology and higher education, one of which is IAIN Sultan Thaha Saifuddin mosque Jambi. The process of registration and processing of data of the recipient bidikmisi in Jambi Sultan Thaha Saifuddin mosque IAIN has not used the integrated information system, thus causing the onset of various obstacles, among others: waste storage media, data access and data updates are slow, the incidence of inconsistencies and redundancies in the data, as well as the lack of accuracy of the data. Grantee information systems bidikmisi in Jambi Sultan Thaha Saifuddin mosque IAIN is designed by using the PHP programming language and uses structured modeling techniques in the form of DFD and ERD to reflect the results of the analysis and design of the system. The output of this research is to design a prototype information system grantee bidikmisi in Jambi Sultan Thaha Saifuddin mosque IAIN, which displays the menu registration participant management, admin, and reports. Expected by the existence of these scholarship recipients information system can contribute to the improvement of information systems scholarship recipients running Sultan Thaha Saifuddin mosque IAIN in Jambi.